Dental Erosion in 10 – 12 Year Old Children in Mosul City (Mustansiria Dental Journal, 2018)
The aim of this study was to determine the prevalence of dental erosion among 10-12 year old children in Mosul city, mean erosion in teeth and surfaces, amount ofcarbonated beverages and fruit juice consumed in the sample, and the correlationbetween dental erosion and some variables. Total sample consisted of 400 childrenderived from different primary schools in the city center. Examination was performedaccording to tooth wear index by Smith and Knight 1984 modified by Millword et al1994.Results showed that dental erosion was highly prevalent 74.2% in the sample,increasing with increasing age, with boys showing a higher prevalence in dentalerosion compared to girls with significant difference. Mean erosion scores for primaryteeth were slightly less then permanent teeth, with a significant difference between 10and 12 years of age for both dentitions.Buccal/labial surfaces exhibited more erosion, followed by lingual/palatal andfinally occlusal /incisal surfaces, with boys showing more erosion in all surfaces thangirls. A large proportion of the sample consumed carbonated beverages 3-5 /weekwith boys consuming more than girls as seen in the erosion group, fruit juice was alsolargely consumed by the sample, especially the group that showed erosion. A positivecorrelation was found between erosion, level of father’s education, time of drinking,method, amount of carbonated beverages and fruit juice consumed.Preventive measures are considered to be the only effective course of managementof dental erosion, by reducing intake of carbonated beverages and fruit juice, alsomodification of erosive drinks, medicines and foods may prove to be an acceptablefuture strategy world wide.